JUVENILE DELINQUENCY IN INDIA- LATEST TRENDS AND ENTAILING AMENDMENTS IN JUVENILE JUSTICE ACT - Agarwal, Deepshikha (PEOPLE: International Journal of Social Sciences, 2018)
Juvenile delinquency is a serious offence and it is detrimental for the social order in any country. There is a trend of increase in juvenile crimes world-over, with more and more involvement of the youth in violent crimes. India shows similar trends of increasing rate of violent crimes committed by the juveniles. It is a very serious concern for the nation and solutions to end the problem need to be sought very carefully. Indian legal system and judiciary has responded to these trends and has brought some amendments in the laws pertaining to juvenile justice in India. This paper aims at looking at the causes of juvenile delinquency and explanations given by scholars from various fields to explain the problem. The analysis of statistical data available at official sites indicates increasing involvement of the juveniles in heinous crimes. To contain the problem of juvenile delinquency in India, the Act pertaining to Juvenile Delinquency has been amended and now trial of juveniles involved in heinous crimes is held as adults.